Occupational trends among UPLB-CA seniors and alumni implications to career guidance - Sto. Domingo, Thelma N. (1977)
This paper determined employment trends among UPLB-CA graduates on one hand, and job preferences and expectations as well as career plans of graduating agriculture students on the other. From these two sample groups, the alumni and the seniors, certain kinds of occupational information were elicited. The Placement Questionnaire was sent by mail to the 1968-1970 and 1974-1975 alumni and the Pre-employment Questionnaire was administered to the seniors who were candidates for graduation. Applying percentage tabulations, ranking, the Z-test, and chi-square analysis, the researcher was able to come up with the findings. Analysis and integration of the findings with some national surveys brought out implications for career guidance.
Appendices: leaves 195-215
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: University of the Philippines (Los Banos) -- Students; Vocational guidance -- Philippines -- Los Banos, Laguna; Occupations